Les réfugiés en Europe, 1936-1948 : la question des motivations - Sharif Gemie; Fiona Reid; Laure Humbert (Les Cahiers de Framespa)
This article discusses the processes of expulsion, exclusion and exile, concentrating on the experience of civilians and non-combatants in the 1930s and 1940s. Several important questions are addressed: what are the factors that transformed ordinary people into the extraordinary ‘refugees’? How did they understand this shift from ‘ordinary person’ to ‘refugee’? Were they a minority, an exceptional part of the population? Or can their experiences be considered as emblematic, even typical of their era?